Differential health effects of short-term exposure to source-specific particles in London, U.K. (December 2016) - Samoli, Evangelia; Atkinson, Richard W; Analitis, Antonis; Fuller, Gary W; Beddows, David; Green, David C; Mudway, Ian S; Harrison, Roy M; Anderson, H Ross; Kelly, Frank J
Abstract: Background: There is ample evidence of adverse associations between short-term exposure to ambient particle mass concentrations and health but little is known about the relative contribution from various sources. Methods: We used air particle composition and number networks in London between 2011 and 2012 to derive six source-related factors for PM10 and four factors for size distributions of ultrafine particles (NSD). We assessed the associations of these factors, at pre-specified lags, with daily total, cardiovascular (CVD) and respiratory mortality and hospitalizations using Poisson regression. Relative risks and 95% confidence intervals (CI) were expressed as percentage change per interquartile range increment in source-factor mass or number concentration. We evaluated the sensitivity of associations to adjustment for multiple other factors and by season. Results: We found no evidence of associations between PM10 or NSD source-related factors and daily mortality, as the direction of the estimates were variable with 95% CI spanning 0%. Traffic-related PM10 and NSD displayed consistent associations with CVD admissions aged 15–64 years (1.01% (95%CI: 0.03%, 2.00%) and 1.04% (95%CI: − 0.62%, 2.72%) respectively) as did particles from background urban sources (0.36% for PM10 and 0.81% for NSD). Most sources were positively associated with pediatric (0–14 years) respiratory hospitalizations, with stronger evidence for fuel oil PM10 (3.43%, 95%CI: 1.26%, 5.65%). Our results did not suggest associations with cardiovascular admissions in 65 + or respiratory admissions in 15 + age groups. Effect estimates were generally robust to adjustment for other factors and by season. Conclusions: Our findings are broadly consistent with the growing evidence of the toxicity of traffic and combustion particles, particularly in relation to respiratory morbidity in children and cardiovascular morbidity in younger adults. Highlights: No associations between source specific particles and mortality. No associations between source specific particles and admissions among the elderly. CVD admissions (15–64 years) associated with traffic or background urban particles. Most particle sources were associated with pediatric respiratory admissions. Fuel oil PM10 strongly associated with pediatric respiratory hospitalizations.